Simbióticos e monensina sódica no desempenho e na qualidade da carne de novilhas mestiças Angus confinadas - Ribeiro, Fábio Garcia [UNESP]; Jorge, André Mendes [UNESP]; Francisco, Caroline de Lima [UNESP]; de Castilhos, André Michel; Pariz, Cristiano Magalhães; da Silva, Maurícia Brandão [UNESP] (FapUNIFESP (SciELO), 2015)
The objective of this work was to evaluate the effect of inclusion of synbiotics and sodic monensin on the performance, carcass characteristics, and meat quality of Angus crossbred heifers on feedlot. A completely randomized block design was carried out with 64 animals distributed in four treatments: control, a diet without supplementation; a diet supplemented with synbiotics; a diet with sodic monensin; and a diet with synbiotics and sodic monensin. The diet with sodic monensin and the diet with synbiotics and sodic monensin increased the average daily gain and total live weight gain, besides improving the feed and biological efficiency of animals compared to control treatment. The diet with synbiotics, with sodic monensin, and with synbiotics and sodic monensin decreased dry matter intake, and increased the rib fillet weight (noix) and the total lipid concentration in the meat. The diet with synbiotics facilitated the reduction of meat shear force compared to control treatment. The inclusion of synbiotics, with or without sodic monensin, in diet of Angus crossbred heifers, improves animal performance on feedlot and some physicochemical characteristics of meat.
Synbiotics and sodic monensin on performance and meat quality of Angus crossbred heifers on feedlot
Keywords: Beef cattle; Body weight gain; Chemical composition of meat; Feed efficiency; Shear force